Renewed Avenues through Exercise Muscle Contractility and Inflammatory Status - Nelo Eidy Zanchi; Felipe Natali Almeida; Fábio Santos Lira; José César Rosa Neto; Humberto Nicastro; Claudia Ribeiro da Luz; Mário Alves de Siqueira Filho; Vitor Felitti; Mariz Vainzof; Marilia Seelaender; Jacques R. Poortmans; Antonio Herbert Lancha (The Scientific World Journal, 2012)
Physical inactivity leads to the accumulation of visceral fat and, consequently, to the activation of a network of inflammatory pathways which may promote development of insulin resistance, atherosclerosis, neurodegeneration, and tumour growth. These conditions belong to the “diseasome of physical inactivity”. In contrast, the protective effect of regular exercise against diseases associated with chronic inflammation may to some extent be ascribed to an anti-inflammatory effect. The so called “acute exercise threshold”, the complex mixture of several variables involved in exercise, such as type, volume, frequency, and intensity range is capable of inducing positive physiological adaptations and has been specifically addressed in the recent literature. The major concern is related to the level of the threshold: “exercise training shifts from a therapeutic adaptive intervention to one with potential pathological consequences”. Nonetheless, if the mechanical stimulus is too weak to disrupt cellular homeostasis, training adaptations will not occur. Answering these questions could present practical applications, especially during inflammatory diseases associated with detrimental muscle effects and could theoretically constitute a “new” therapeutic approach to treat/improve an inflammatory state. This paper aims to describe specific data from the literature regarding the effects of exercise on inflammatory diseases in order to promote a more sophisticated perspective on the anti-inflammatory effects of exercise.